2010
DOI: 10.1016/j.ccr.2009.12.034
|View full text |Cite
|
Sign up to set email alerts
|

MLL-AF9-Induced Leukemogenesis Requires Coexpression of the Wild-Type Mll Allele

Abstract: SUMMARY Oncogenic fusion proteins are capable of initiating tumorigenesis but the role of their wild-type counterparts in this process is poorly understood. The mixed lineage leukemia (MLL) gene undergoes chromosomal translocations, resulting in the formation of oncogenic MLL fusion proteins (MLL-FPs). Here we show that menin recruits both wild-type (wt) MLL and MLL-AF9 to the loci of Hox genes to activate their transcription. Wild-type MLL not only catalyzes histone methylation at key target genes but also co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
195
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 213 publications
(215 citation statements)
references
References 48 publications
12
195
4
Order By: Relevance
“…36 Whether wild-type MLL is also required for the development or maintenance of t(4;11)-positive leukemias remains uncertain. However, as we show in this study, epigenetic inactivation of miR-152 at least prevents the downregulation of wild-type MLL.…”
Section: Discussionmentioning
confidence: 99%
“…36 Whether wild-type MLL is also required for the development or maintenance of t(4;11)-positive leukemias remains uncertain. However, as we show in this study, epigenetic inactivation of miR-152 at least prevents the downregulation of wild-type MLL.…”
Section: Discussionmentioning
confidence: 99%
“…84 MLL wild-type, AF4-MLL and DNMT1 were identified as potential target genes for miR-152 based on 3 0 UTR sequence homology. 79 This is of high interest because the co-expression of MLL wild-type is facilitating MLL-AF9-induced leukemogenesis 85 and the AF4-MLL reciprocal fusion protein contributes to leukemic transformation. 86 Moreover high levels of DNMT1 may be responsible for the genome-wide hypermethylation that characterizes t(4;11)/AF4-MLL-positive ALL and was linked to an increased risk of relapse.…”
Section: Using Epigenetic Drugsmentioning
confidence: 99%
“…Further studies indicate that the wild-type MLL allele is required for MLL-AF9-induced leukemogenesis. Wild-type MLL controls both H3K4 methylation and MLL-AF9-induced H3K79 methylation (Thiel et al, 2010). Aggressive histone modifications in 5 0 Hoxa cluster gene expression (Yan et al, 2006a) and promoter DNA methylation (Bullinger and Armstrong, 2010) substantially contribute to leukemic cell phenotypes.…”
Section: Failure Of Maintenance Of Hox Genes In Leukemia Cellsmentioning
confidence: 99%
“…Increasing evidence suggests that Hox transcription factors play a definitive role in normal proliferation and differentiation of hematopoietic cells (Magli et al, 1997;Owens and Hawley, 2002). Recent discoveries revealed that the menin and MLL-containing histone methyltransferase complex is required for Hox gene-dependent proliferation and differentiation of hematopoietic progenitors and leukemia stem cells (Hess, 2004;Hughes et al, 2004;Milne et al, 2005;Yokoyama et al, 2005Yokoyama et al, , 2010Chen et al, 2006;Thiel et al, 2010). These studies have given emphasis to epigenetic regulations in Hox-dependent hematopoiesis and leukemogenesis.…”
Section: Introductionmentioning
confidence: 99%